The English Learning Effort: Optimizing English Speaking Skills Through Total Physical Response Method for Fourth Grade Elementary School at Kuala Lumpur of Indonesian School (SIKL) - Achmad Haqqul Yaqin; Juhaeni; Taufik; Deany Yasir (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research was motivated by the problem of difficulty speaking English in grade 4 elementary school students due to lack of mastery of vocabulary and correct pronunciation. Only 5% of all students are skilled in speaking English. This was proven when teachers demonstrated daily activities such as reading books, 75% were unable to mention the correct vocabulary. Apart from that, the lack of interactive teacher methods is used as one of the factors preventing students from practicing English in everyday life. So this research aims to optimize the English speaking skills of 4th grade elementary school students through one method, namely the total physical response (TPR) method. The existence of this method plays a direct role in both teachers and students in imitating all activities with body movement. Its more interactive application means that students do not get bored and fed up easily when learning takes place. As a form of supporting its success, researchers used descriptive qualitative methods through observation, interviews with both teachers and students. The implementation involved 4th grade elementary school students at the Kuala Lumpur Indonesian School. The research results showed that 30 out of 34 students were able to apply the total physical response method as an effort to optimize English speaking skills in their surroundings. One application with the teacher is by doing storytelling in front of the class about the activities carried out throughout the day